Peroxidation of blood plasma lipids after various regimes of external irradiation of rats by 60Co gamma-rays - M. Vatankhan; A. I. Lypska; Ya. I. Serkiz (Ядерна фізика та енергетика)
Peroxidation products of lipids in blood plasma of laboratory rats are studied after one-time, fractional and long-term external irradiation of the rats by 60Co gamma-rays. It was found, that different modes of a total external irradiation of rats lead to prominent features of dynamics and dose dependences of radio gene changes of the content of peroxidation products of lipids in blood plasma. It was shown that fractional irradiation is less effective for an organism, whereas long-term irradiation causes essentially big radiation induced changes than one-time action of radiation.